MODEL PEMBELAJARAN SENTRA DAPAT MENGEMBANGKAN SIKAP BERSOSIAL UNTUK ANAK USIA TAMAN KANAK KANAK - achmadi achmadi (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2019)
Early childhood is the development of all aspects of life both in physical and psychological aspects. One of them is social and emotional development.. The background in this research is to study the development of social and emotional aspects of children through center learning models. The fact that the Center learning model is to provide the opportunities students for societal and good behavior. Besides that, the Center learning model is centered for the children. The children are given the freedom to choose their friends and to carry out for the types of assignments are given by their teachers.Through the Center learning model will perform good social and emotional behavior. In addition, the BCCT learning model or Center model comes down to the chilhood’s achievement in theall aspects’ human development. Therefore, this learning model should be planned carefully through the various tool’s playing (playing activities) to facilitate the achievement of the children’s development. The goal of the research is to know the development of the social’s child and emotional attitudes through the Center learning model. Type of this research is quantitative research two group design. The subjects research by using the children as many as 24 children are divided two groups. 12 children are as the control group, and 12 children as the experimental group. For analysis data by using the different velue between the control group and the experimental group. The result is the probability of sig is 0.178 and the significant in 5% is 0.025 . The conclusion in this research iis The Center learning model can not form the societal and emotional.behavior for early childhood in TK Sunan Cendono Kecamatan Kwanyar Kabupaten Bangkalan.